2019
DOI: 10.3390/ijerph16183331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Undergraduate Students’ Responsiveness to a 4-Week University-Based Animal-Assisted Stress Prevention Program

Abstract: An increase in the prevalence of stress among college students is compromising their mental health and academic success. One approach to stress prevention that has seen a surge in implementation is the use of university-based Animal Visitation Programs (AVPs). Despite their popularity and promising causal findings, program evaluations on students’ responsiveness (e.g., enjoyment, attendance, perceptions on usefulness and behavioral change) have yet to be conducted. Using a mixed methods approach, this study re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
2
17
0
1
Order By: Relevance
“…While speculative, the overall results resonate with findings from a previously published program evaluation [45] where we examined participants' responsiveness to animal assisted programming activities. The results of qualitative analyses based on participant responses to open-ended, anonymous survey questions, showed that interacting with a therapy dog may have served as a positive and rewarding stimulus that became associated with the participation in content presentations.…”
Section: Discussionsupporting
confidence: 77%
“…While speculative, the overall results resonate with findings from a previously published program evaluation [45] where we examined participants' responsiveness to animal assisted programming activities. The results of qualitative analyses based on participant responses to open-ended, anonymous survey questions, showed that interacting with a therapy dog may have served as a positive and rewarding stimulus that became associated with the participation in content presentations.…”
Section: Discussionsupporting
confidence: 77%
“…Although providing this kind of intervention to college and university students is a fairly new undertaking [ 26 ], there is promising evidence that AAIs can, amongst others, result in higher ratings of momentary positive emotions, a reduction in stress-related negative emotions [ 27 , 28 ], psychological and physical markers of stress [ 29 , 30 , 31 , 32 ], anxiety [ 33 , 34 , 35 , 36 ], and homesickness while increasing their satisfaction with life, connectedness to campus [ 37 , 38 ], behavioral aspects of academic success [ 39 ], well-being and improving their social skills as well as their mood [ 29 , 33 , 40 ]. Furthermore, Daltry and Mehr [ 41 ] found that having animals on campus may promote the services offered by student counseling centers on campus, as a lot of students were unaware of them before implementing the AAI.…”
Section: Introductionmentioning
confidence: 99%
“…Students’ attitude towards the dog-assisted intervention (DAI) was not evaluated. However, a study by Pendry et al [ 30 ] showed that students associate the combination of evidence-based academic stress management content and AAI with a higher degree of enjoyment, perceived benefit and likelihood of recommendation compared to content presentation or AAI alone. Yet, studies examining attitudes toward DAI in particular exist only in the context of Spanish and Romanian students [ 40 , 51 , 52 ], reporting a positive attitude and high interest in DAI.…”
Section: Introductionmentioning
confidence: 99%
“…This may also explain why the effects of HAI only exposures showed more pronounced effects at follow-up for at-risk students on global EF and metacognition compared with sessions that incorporated stress management information. In fact, a prior study found that students expressed that interacting with animals was relaxing and enjoyable, while receiving information was stressful or redundant (Pendry, Kuzara, et al, 2019). Although risk status was not considered in those findings, some students expressed that receiving information only served to conjure thoughts of stressful situations or realities without providing a means of remedying the source of the stress.…”
Section: Discussionmentioning
confidence: 99%